Challenges in Assessing the Costs of Household Cooking Energy in Lower-Income Countries - Toman, Michael (World Bank, Washington, DC, 2017)
The paper discusses challenges in analyzing the costs of household cooking methods (fuels and associated stove technologies) in lower-income countries, and sources of divergence between observed and true social costs. The challenges in assessing social costs include valuation of household time, impacts of credit constraints on stove selection, preferences for stove characteristics, and the magnitude of health and environmental externalities. All these influences on cost require consideration of the local context.